Needle and syringe sharing practices of injecting drug users participating in an outreach HIV prevention program in Tehran, Iran: A cross-sectional study - Kihara Masahiro; Ono-Kihara Masako; Zamani Saman; Nassirimanesh Bijan; Vazirian Mohsen; Mortazavi Ravari Shahrzad; Gouya Mohammad (BMC, 2005)
Abstract HIV infection rates have reached epidemic proportions amongst injecting drug users (IDUs) in Iran. Although a number of community-based interventions have being implemented in the country, there is little information on the risk behaviors of IDU participants in these programs. This cross-sectional report aimed to compare the risk behaviors of injecting drug users with differential exposure rates to an HIV outreach program in Tehran, Iran. Results indicated that shared use of needle/syringe in the past month was significantly lower among IDUs who received estimated ≥ 7 syringes per week than those who did not [adjusted odds ratio (OR) = 14.36, 95% confidence interval (CI) 2.30-89.56]. While the effectiveness of this outreach program needs further evaluation through a longitudinal investigation, our preliminary findings suggest that the outreach program in Tehran may have been beneficial in reducing direct sharing among those who received more than several needles/syringes from the program.